Neural learning algorithm for halftoning - Tuttaß, T.; Bryngdahl, O. (Optics communications, 1995)
Most processes used for halftoning consist of linear and nonlinear elements. Neural networks offer the possibility of combining these elements in a general and flexible structure. Image binarization methods can be analysed and transfered to neural structures and typical neural learning algorithms offer new ways to treat the halftoning problem. We examine a simple learning algorithm and demonstrate the difficulties and possibilities concerning the halftoning problem.